Comparison of the ergonomics of plating techniques - Pyatkovsky, Taras; Pokryshko, Olena (Annals of Mechnikov's Institute, 2023)
Introduction. Bacteriological method with plating techniques is often used for routine microbiological studies. Ergonomics is an important component of the safety and efficiency of work in a microbiological laboratory, the duration of microbiological studies can affect the results and productivity of the laboratory. Routine microbiological studies require the use of disposable and reusable materials and time consumption. Various methods maintain the sterility of experimental materials and allow the successful isolation of bacterial colonies. For plating of liquid samples from the patients or bacterial suspensions in Ukraine, disposable plastic or glass and metal reusable Drigalski spatulas are used. Abroad, for this purpose, in addition to spatulas, the Copacabana spreading method (also known as the bead method) is also used. Material & methods. Two strains of E. coli ATCC 25922 and S. aureus ATCC 6538 obtained from the culture collection of the Laboratory of Microbiological and Parasitological Research of TNMU were used for the experiments. Drigalski L-shaped glass spatulas with a diameter of 3.6 mm and a length of the working surface of 30.0 mm and glass beads with a diameter of 3.7 mm were used for plating of the suspension of microorganisms. For the experiments, a suspension of each strain was prepared from a broth. The cultures were centrifuged and the pellets were resuspended in sterile physiological solution. Serial dilutions of the suspensions were carried out with plating of 100 μl aliquots on meat peptone agar (MPA) in plastic Petri dishes. Escherichia coli suspensions were additionally plated on Endo agar. Petri dishes were incubated at 37 °C for 24-48 h, followed by colony counting. The time for preparation and conducting the experiment was recorded. Time for wrapping spatulas, preparation of test tubes with balls, time for spreading the inoculum by these means was taken into account. Average values of the number of colony-forming units (CFU), expressed in logarithmic values, were used for statistical analysis. The experiment was performed in triplicates, comparison of means was performed using the Student's t-test. Differences at p < 0.05 were considered significant. Results & discussion. The time for preparing materials and carrying out inoculation was shorter for spatulas. The total time when using spatulas to inoculate five Petri dishes turned out to be shorter on average by 19.4 seconds. The colonies distribution was visually better with the beads method. Plating a dense suspension of microorganisms produced noticeable clusters of colonies. The total plating surface area of the beads exceeded the plating area of the working surface of the spatula by approximately 7.7 times. It was 112.6 mm2 for the spatula, and 866.8 mm2 for the beads. However, such a difference did not influence the numbers of counting colony-forming units produced by using these methods. There were no statistically significant difference when inoculating S. aureus ATCC 6538 suspension on MPA (p = 0.48) and E. coli ATCC 25922 suspension on MPA and Endo agar (p = 0.43). Conclusion. The Copacabana method takes more time to prepare and use, but gives better results in dispersing bacteria over the surface of solid culture media to obtain isolated colonies. According to the results of counting colony-forming units, plating with glass beads corresponds to plating with a spatula. The beads method can be used in microbiological studies using serial dilutions for plating large numbers of Petri dishes.